Iron ore sintering. Part 3: Automatic and control systems (2015)
The sintering process involves a large number of parameters, more than 500, each of which exerts a greater or lesser influence and needs to be controlled, within the possible limits, in order to optimise productivity, process stability, and standardise the composition and quality of the sinter produced. To comply with environmental legislation, a pollution control system must monitor the particle matter and gases generated and emitted into the atmosphere by the sinter plant. Automation and control systems are vital tools to assist plant operators in the monitoring of each stage of the sinter production process.